2023
DOI: 10.1007/s12325-023-02659-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tezepelumab on Lung Function in Patients With Severe, Uncontrolled Asthma in the Phase 3 NAVIGATOR Study

Andrew Menzies-Gow,
Christopher S. Ambrose,
Gene Colice
et al.

Abstract: Introduction: Severe asthma is associated with airway inflammation and airway obstruction. In the phase 3 NAVIGATOR study, tezepelumab treatment significantly improved pre-bronchodilator forced expiratory volume in 1 s (FEV 1 ) compared with placebo in patients with severe, uncontrolled asthma. This analysis assessed the effect of tezepelumab versus placebo on additional lung function parameters in patients from NAVIGATOR. Methods: NAVIGATOR was a multicenter, randomized, double-blind, placebo-controlled study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Additional analysis showed that tezepelumab markedly reduced exacerbations precipitated by exposure to specific seasonal and perennial aeroallergens during periods of heightened exposure. This evidence demonstrated that the allergenic trigger could induce epithelial-driven exacerbations that tezepelumab is able to control (47). The phase 3 trial SOURCE showed a non-significant difference between treatment and placebo at 48-weeks on Oral Corticosteroids (OCS)-sparing effect (48).…”
Section: Tezepelumab: Anti-tslpmentioning
confidence: 97%
“…Additional analysis showed that tezepelumab markedly reduced exacerbations precipitated by exposure to specific seasonal and perennial aeroallergens during periods of heightened exposure. This evidence demonstrated that the allergenic trigger could induce epithelial-driven exacerbations that tezepelumab is able to control (47). The phase 3 trial SOURCE showed a non-significant difference between treatment and placebo at 48-weeks on Oral Corticosteroids (OCS)-sparing effect (48).…”
Section: Tezepelumab: Anti-tslpmentioning
confidence: 97%